Medikamentöse Therapie in der interventionellen Radiologie = Drug therapy in interventional radiology - Sumkauskaite, Migle; Bryant, Mark; Kortes, Nikolas; Stampfl, Ulrike; Radeleff, Boris (Der Radiologe, 2015)
In the context of pre-interventional drug therapy, a premedication is given to patients who are known to have an allergy to contrast media, have renal impairment or hyperthyroidism. An already existing anticoagulation therapy, in anticipation of the planned intervention, must be reviewed and changed or even suspended as required. For peri-interventional drug therapy it is important to consider how strenuous the procedure will be as well as the general condition of the patient. Further discussion with anesthetists may be required for the planning of pain therapy or sedation during the procedure. These factors help to ensure maximum patient comfort as well as the success of the intervention. Post-interventional anticoagulation therapy, usually started peri-interventionally, plays an important role in minimizing the risk of acute thrombosis as well as in maintaining long-term functioning of the implanted material. The form of the anticoagulation therapy is set according to the type of intervention.